ARABIC TRANSLATION TECHNIQUES OF COVID-19 TERMS IN THE DAILY ARABIC NEWSPAPER OF INDONESIAALYOUM.COM - Adrian Surya Da Cunha; Yoyo Yoyo; Abdul Razif Zaini (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
As an international language, Arabic develops continuously. Arabic development in various fields was triggered by the development of science, technology, and arts. This development continues to be carried out by adapting and translating new terms, forming new terms, absorbing them from the source language, and harmonizing with Arabic rules. This research is qualitative with a library research approach and uses the descriptive analysis method. This study aims to analyze the technical translation of the covid-19 terms in Arabic on the news page "indonesiaalyoum.com." The study found twelve Arabic terms on Covid-19 on the news page of “indonesiaalyoum.com” Meanwhile, on the translation techniques, there are seven techniques used for the translations of covid-19 terms on the “indonesiaalyoum.com” news page. Those techniques are borrowing, amplification, description, adaptation, transposition, and standard equivalence. However, the more dominant technique used is the literal translation technique. The Arabic translation of the Covid-19 terms adopts original words from the source language.